2020
DOI: 10.1002/jor.24613
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of posterior‐stabilized, cruciate‐retaining, and medial‐stabilized knee implant motion during gait

Abstract: Accurate knowledge of knee joint motion is needed to evaluate the effects of implant design on functional performance and component wear. We conducted a randomized controlled trial to measure and compare 6-degree-of-freedom (6-DOF) kinematics and femoral condylar motion of posterior-stabilized (PS), cruciate-retaining (CR) and medial-stabilized (MS) knee implant designs for one cycle of walking. A mobile biplane X-ray imaging system was used to accurately measure 6-DOF tibiofemoral motion as patients implanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 41 publications
5
85
0
Order By: Relevance
“…The study was conducted with a population of 15 healthy individuals (9 males and 6 females), and assessed movements and rotations including flexion-extension, internal-external rotation, and abduction-adduction. The data collected from this study yielded valuable information for the assessment of knee function in normal and pathologic gait [16]. The findings in this study support the hypothesis that portable xrayimaging is useful as a diagnostic instrument of certain components of the knee.…”
Section: Discussionsupporting
confidence: 72%
“…The study was conducted with a population of 15 healthy individuals (9 males and 6 females), and assessed movements and rotations including flexion-extension, internal-external rotation, and abduction-adduction. The data collected from this study yielded valuable information for the assessment of knee function in normal and pathologic gait [16]. The findings in this study support the hypothesis that portable xrayimaging is useful as a diagnostic instrument of certain components of the knee.…”
Section: Discussionsupporting
confidence: 72%
“…For the first time, we reported the knee kinematics of MP and PS TKA of Chinese patients in this study with the anatomical coordinate system and femoral transepicondylar axis. Gray et al (2020) reported similar peak flexion angle at mid-swing in the MP and the PS TKA (MP 52.5 vs. 54.8° PS, p = 0.64), which was less than healthy knees [70.7° by Gray et al (2019) and 65.6° by Postolka et al (2020) ]. In our study, the two TKA groups showed similar peak flexion angles (MP 52.4 ± 7.4 vs. 50.1 ± 3.6 PS, p = 0.47) and were consistent with previous studies ( Yoshida et al, 2012 ; Arauz et al, 2018 ; Grieco et al, 2018 ; Gray et al, 2020 ).…”
Section: Discussionmentioning
confidence: 73%
“… Gray et al (2020) reported similar peak flexion angle at mid-swing in the MP and the PS TKA (MP 52.5 vs. 54.8° PS, p = 0.64), which was less than healthy knees [70.7° by Gray et al (2019) and 65.6° by Postolka et al (2020) ]. In our study, the two TKA groups showed similar peak flexion angles (MP 52.4 ± 7.4 vs. 50.1 ± 3.6 PS, p = 0.47) and were consistent with previous studies ( Yoshida et al, 2012 ; Arauz et al, 2018 ; Grieco et al, 2018 ; Gray et al, 2020 ). To note, different from TKA knees in other studies of Caucasian patients ( Hanson et al, 2006 ; Gray et al, 2020 ), no flexion peak in the early-stance phase was found in our patients ( Figure 3A ).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Typically, in the case of knee osteoarthritis, the contact point trajectories, among other joint and muscle factors, are modified by the pathology (Scarvell et al, 2018) and restored by the arthroplasty (Li et al, 2015). The alteration of the contact points appears to be a clinically relevant parameter to assess joint pathology (Farrokhi et al, 2014;Zeighami et al, 2017) as well as prosthetic performance (Gray et al, 2020;Nicolet-Petersen et al, 2020). For instance, the contact point trajectories can help estimating the in vivo slip velocity (Andriacchi et al, 2003;Dumas et al, 2020a;Hamilton et al, 2005) which is an important parameter, together with the estimated in vivo contact force, for characterising wear in the prosthetic components.…”
Section: Discussionmentioning
confidence: 99%